2016
DOI: 10.1073/pnas.1607147113
|View full text |Cite
|
Sign up to set email alerts
|

WD40 domain of Apc1 is critical for the coactivator-induced allosteric transition that stimulates APC/C catalytic activity

Abstract: The anaphase-promoting complex/cyclosome (APC/C) is a large multimeric cullin–RING E3 ubiquitin ligase that orchestrates cell-cycle progression by targeting cell-cycle regulatory proteins for destruction via the ubiquitin proteasome system. The APC/C assembly comprises two scaffolding subcomplexes: the platform and the TPR lobe that together coordinate the juxtaposition of the catalytic and substrate-recognition modules. The platform comprises APC/C subunits Apc1, Apc4, Apc5, and Apc15. Although the role of Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…One possible explanation for this result is that UBE2S CTP -dependent activation mimics coactivator-induced activation where a conformational change in the catalytic core allows for UBE2C recruitment. Previous studies revealed that the N-terminal WD40 domain of APC1 is necessary for this coactivator-dependent conformational change 26 . These studies show that deletion of the WD40 domain (APC/C ΔAPC1-WD40 ) locks the APC2–APC11 catalytic core in a “downward” conformation similar to the apo state rendering the UBE2C-binding site inaccessible in the presence of coactivator ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation for this result is that UBE2S CTP -dependent activation mimics coactivator-induced activation where a conformational change in the catalytic core allows for UBE2C recruitment. Previous studies revealed that the N-terminal WD40 domain of APC1 is necessary for this coactivator-dependent conformational change 26 . These studies show that deletion of the WD40 domain (APC/C ΔAPC1-WD40 ) locks the APC2–APC11 catalytic core in a “downward” conformation similar to the apo state rendering the UBE2C-binding site inaccessible in the presence of coactivator ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… a , Cartoon representing APC/C ΔAPC1-WD40 showing the catalytic core locked in a downward position and inaccessible for UBE2C recruitment, based on previous studies 26 . b , Substrate ubiquitination reactions comparing the effects of UBE2S CTP and UBES CTP−4A (residues 219-222 of UBE2S CTP substituted for alanine) on CycB NTD * priming, multiubiquitination, and Ub chain elongation by APC/C ΔAPC1-WD40 , UBE2C, and UBE2S.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitylation of a substrate not only depends on its binding to Cdh1, but also on its relative position and proximity to the K11-linking machinery [39]. We determined that both wild type and ST/A E2F1 bind to Cdh1.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by real-time cell cycle microscopy revealed a significant delay within the interphase for synchronized fibroblast cells derived from individuals with the intronic splicing mutation compared to control fibroblasts ( Figure 3A). There 24,25 The WD40 domain mediates conformational changes important for stimulating the APC's catalytic activity upon co-activator binding. The Mid-N and Mid-C domains coalesce together in the APC complex.…”
mentioning
confidence: 99%